Chemoprevention in patients with genetic risk of colorectal cancers. (June 2012) - Laukaitis, Christina M; Erdman, Steven H; Gerner, Eugene W
SUMMARY  A number of genetic syndromes are known to convey a high risk of colorectal cancer. Current standards of medical practice for these patients involve genetic testing followed by screening and surgical procedures. Pharmaceutical therapies for any of these syndromes are limited in number and are generally not approved by any regulatory body for applications in these genetic groups. This review discusses advances in mechanistic understanding of the disease processes leading to the development of promising pharmaceutical therapies. Clinical trials of potential chemotherapeutic agents must focus on the reduction of disease-related events, including cancer and cancer-related mortality, in patients with genetic syndromes.